Detection of Escherichia coli O157:H7 in the beef marketed in Malaysia - Radu, Son; Abdul Mutalib, Shahilah; Rahmat Ali, Gulam Rusul; Ahmad, Zainori; Morigaki, Tadaaki; Asai, Norio; Kim, Yung Bu; Okuda, Jun; Nishibuchi, Mitsuaki (American Society for Microbiology, 1998)
Twelve strains of Escherichia coli O157:H7 were isolated from 9 of 25 beef samples purchased from retail stores in Malaysia. These strains produced Shiga toxin 2 with or without Shiga toxin 1 and had the eae gene and a 60- MDa plasmid. The antibiograms and the profiles of the arbitrarily primed PCR of the strains were diverse, suggesting that the strains may have originated from diverse sources.